Caracterização estrutural do Lineamento de Piúma e sua influência na porção norte da Bacia de Campos - Bronzoni, Letícia Cornachini [UNESP] (2011)
The detailed study of the Brazilian continental margin basins became possible with the advancement of geophysical tools, with emphasis on seismic reflection. Characterizing the structural and stratigraphic elements of Brazil’s marginal basins they realized that there was a relationship with structures present on the adjacent continental basement. So many works began to be made to understand this relationship and know the major factors that influenced the evolution of the continental margin. The study area of this work includes the northern portion of the Campos Basin and the continental outcropping adjacent areas, which corresponds to the northern of Rio de Janeiro state and the southern of Espirito Santo state. This area stands an important structural feature of NW-SE direction with a projection to the Campos Basin called Lineamento de Piúma. The outcropping basement rocks belongs to the Ribeira Belt which was bonded to other mobile bands forming the continent Western Gondwana during the Brasiliano Cycle, which later fragmented giving rise to the Atlantic Ocean. The opening of the ocean results on the formation of the marginal basins of Brazil. These basins have continental, transitional and marine facies. On Campos Basin the continental phase resulted on the formation of horsts and grabens bounded by synthetic and antithetic faults. Continuing rifting formed the saline lakes that deposited siliciclastic and carbonate sediments. The transitional phase resulted on thick packages consist of evaporites (halite and anhydrite) that was deposited in lagoon environment, tectonically quiet arid and semi-arid. The marine phase it deposited siliciclastic and carbonate in the Campos Basin resulting in shales, marls, limestones, ritmito, turbidites, sandstones and others. The objective of this study is to investigate the possible continuation... (Complete abstract click electronic access below)